ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP MARKET VALUE ADDED (MVA) PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sunarko, Bambang; Martini, Sri (Performance, 2011)
This research is an empirical study to analyze the data causally (cause and effect). This research entitled by: "Impact Analysis of Earnings, Operating Cash Flows, Economic Value Added (EVA) and DR to the Market Value Added (MVA)". The aim of this study was to determine the performance of manufacturing firms in Indonesia Trade Center. In addition, this study also aimed to determine the influence of Earnings, Operating Cash Flow, Economic Value Added (EVA) and DR to the Market Value Added (MVA). Population in this research are manufacturing companies that listing on the Indonesia Trade Center. Determination of the sample is done by purposive sampling method. The number of companies that used a sample of 23 companies. Period of research is 3 years during 2006 until 2008. Based on the results of research known that the performance of manufacturing firms in Indonesia Trade Center was good. By analysis of data using multiple regression showed that (1) Earnings significantly affect the Market Value Added (MVA), (2) Operating cash flow is not significantly affect the Market Value Added (MVA), (3) Economic Value Added (EVA) not significantly affect to the Market Value Added (MVA),(4) Debt Ratio (DR) significantly affect to the Market Value Added (MVA), (5) Simultaneously, Earnings, Operating Cash Flow, Economic Value Added (EVA) and DR significantly affect the Market Value Added (MVA), and (5) Operating Cash Flow is the most influential variable on Market Value Added (MVA). The implications of the conclusions above are in decision-making, both managers and investors, should see the company's performance. These performance indicators can be seen through Earnings, Operating Cash Flow, Economic Value Added (EVA) and Debt Ratio (DR).